Usaha Pemasaran Produsen Tempe - Kusdiana, R. Nana; Septyoari Putranto, Trias (Binus Business Review, 2013)
Tempe is a food made from the fermentation of soybeans or some other materials using somekind of fungus Rhizopus, such as Rhizopus oligosporus, Rh. oryzae, Rh. stolonifer or also known as bread mold, or Rh. arrhizus. Fermentation preparations are commonly known as "yeast tempe". Tempe has been known since ancient times, particularly in Java as supplement staple food which is high protein and low cholesterol. Tempe and tofu selling price is still low compared to other protein food sources, such as fish and chicken. According to market research, the majority of tempe and tofu products is still the lower classâ consumption, since the quality and processing methods are traditional distribution, including in sanitation and hygiene. It is necessary to stimulate and generate interest in the bank to develop relationship with the Indonesian Tofu Tempe Producers Cooperative (KOPTI) and its members to tempe producers can increase production and performance. Tempe and Tofu Development Centers Manufacturers through Integrated Partnership Program by KOPTI as a company with a core group of tempe and tofu manufacturers, which are members of the KOPTI, is the modernization of tempe and tofu small business activity to be an independent food business industry.